Meta Verified Trends in Indonesia Related to Brand’s Endorsement Decisions - Putri, Vega Karina Andira; Dinansyah, Fakhriy (Jurnal Audience: Jurnal Ilmu Komunikasi, 2024)
In June 2023, Meta Verified has been available and can be purchased in Indonesia. Meta Verified is a service that allows all Instagram and Facebook users to get a blue tick and several other benefits the company offers. The interest of Instagram users in subscribing to this service is immense because a blue tick accompanying the account name is considered to strengthen an individual's profile. The blue tick is believed to support the personal branding built by someone on Instagram to become more credible. So far, brands have a preference for choosing accounts with a blue tick because they are synonymous with their credibility in the eyes of the public. Aditya's research in 2021 shows that the source's credibility increases awareness of the company and can determine the attitude of Indonesian consumers towards a brand advertisement. The presence of Meta Verified, which now allows all users to have a blue tick without showing credibility, is the background to the paper entitled "Meta Verified Trends in Indonesia Regarding Endorsement Decisions by Brands." This research aims to determine whether there has been a change in the preferences of endorsers who have blue ticks on Instagram. This research paper uses a case study method with data collection techniques through interviews with brands who frequently endorse on Instagram social media. This research shows that brands place a larger endorsement budget for Instagram accounts with a blue tick that does not use subscription services or for those that get the blue tick organically.Keywords: Meta Verified, Personal Branding, Endorsement, Social Media, Innovation